Sustainable models of OER - Morgado, Lina (2015)
The objetive of Training Material "OER and Sustainability Models" is to train trainers and it is organised in 3 Units. The learner will be able to: i) understand the approach of open movement; ii) describe/identify specific characteristics of OER; iii) find, select and use/reuse/make one OER; iii) analyse case studies of sustainable models of OER. The Unit 3 focus is to analyse three different cases of sustainable models of OER. The content is an OER.